Two new species of the Clubiona corticalis group (Araneae, Clubionidae) from Yunnan, China - Minghao Guo; Zhaoyi Li; Feng Zhang (ZooKeys)
Two new species belonging to the corticalis group of the sac spider genus Clubiona Latreille, 1804 are described from both males and females: Clubiona longyangensis sp. nov. and Clubiona multiprocessa sp. nov. The two species are currently known to occur in Baoshan City and Dali Bai Autonomous Prefecture, Yunnan, China, respectively. Detailed descriptions, diagnoses, and photographs of the two species are provided.